Pendidikan Kewarganegaraan Sebagai Pendidikan Karakter: Analisis Kritis Terhadap Pendidikan Kewarganegaraan di Indonesia - Devinda Ramdani; Ameliya Ameliya; Kharisma Fresty; Ilham Hudi (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
Citizenship education has been recognized as an important element in shaping the character of individuals and society. However, its implementation in Indonesia raises critical analysis. This paper explores various aspects of citizenship education in Indonesia, including curriculum, teaching methods, and evaluation. Critical analysis is carried out on its effectiveness in forming character, overcoming challenges, and improving the quality of democracy. Apart from that, aspects of inclusivity, diversity and relevance in the context of diverse societies in Indonesia are also paid attention to. The results of this analysis provide insight into the efforts needed to strengthen citizenship education as an inclusive and relevant character builder in the Indonesian context.